Hur påverkar belöningssystem ett medelstort detaljhandelsföretags arbete inom kundrelationer? - Hansen, Elisabeth; Johansson, Anna (2014)
Retail companies want to develop long-term customer relationships to maintain their position in the market where customers have many stores to choose from for the same type off products. The company uses a reward system to motivate their employees to develop a good customer relationship with customers entering their store. This thesis will examine the work of customer relationship management, also called CRM, and reward system. The thesis will examine a mid-sized retail business in Luleå working with collective reward system and CRM work. Interviews were conducted individually with four representatives from the working team and one from the management of the store. The conclusions is that when individuals are aware of what is expected of their work, the individual will work toward organizational goals and not merely its pursuit of a bonus. This paper has resulted in the information distribution that in the use of reward systems as a motivation tool must be made to all employees at a workplace in order to build sustainable and long-term customer relationships. Validerat; 20140821 (global_studentproject_submitter)